ISLAMIC ARCHITECTURAL CONCEPT IMPLEMENTATION IN SHARI’AH BRANDING HOUSING AT BARAZAKI RESIDENCE, DEPOK, WEST JAVA - Sarah Aisha; Marselly Dwiputri; Rafi Mentari (Lakar: Jurnal Arsitektur, 2023)
Islamic housing design concepts can be explored and inspired in designing built environments with Islamic values in Indonesia. Currently, new housing is mushrooming that is being offered by developers. One of the branding strategies undertaken by developers in the city of Depok is to promote shari'ah branding in sales. The purpose of this study focuses on housing that uses the Shari'ah branding strategy in the city of Depok by exploring whether the housing also uses the concept of Islamic architecture. The method used in this study is to use a qualitative descriptive method, where the selection of housing samples has been determined and carried out an assessment based on the data that the author has, namely housing with sharia branding that uses an Islamic architectural style. Previous research discussed the shape, pattern, and character of Islamic residential houses. Meanwhile, in this research, a typological study was carried out on the arrangement of Islamic residential areas, with limited physical and philosophical studies. Based on the results of qualitative research on the Implementation of Islamic Architecture Concepts in Barazaki Residence Housing, Depok, the concept of Islamic Architecture has not been applied either to the principles of architectural appearance or the principles of Islamic architectural space.